The effect of lexical triggers on Spanish-English code-switched judgment tasks - Koronkiewicz, Bryan; Delgado, Rodrigo (Frontiers in Psychology, 2024)
Introduction It has been argued that certain words can “trigger” intrasentential code-switching. While some researchers suggest that cognates establish triggering at the lexical level, others have argued that words that lack direct translations are more natural stories switch. Yet to be tested experimentally is to what extent different types of lexical items influence the acceptability of mixed utterances. Methods The current study investigates this methodological consideration for code-switching research by having early US Spanish-English bilinguals (i.e., heritage speakers of Spanish) complete an acceptability judgment task with a 7-point Likert scale directly comparing cognates (e.g., sopa “soup”) and culturally specific items (e.g., pozole “traditional Mexican soup”) in otherwise identical grammatical switched sentences (N = 24). Results The results showed that there was no significant effect of condition (p = 0.623) suggesting that cognates and language-specific items are equally acceptable in code-switched sentences. Indeed all conditions were rated on average above 6. Discussion These findings show that in this context, judgment tasks are not affected differently by these types of lexical items.